Pengembangan Inovasi Pembelajaran Menggunakan Papan Pintar Matematika Pada Materi Operasi Hitung di Sekolah Dasar - Asuta, Chelsie; Nurani, Tirta; Putri, Winda Anika (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2024)
Smart mathematics board is a technological innovation that combines the traditional concept of learning mathematics with elements of advanced technology. This smart board is designed to improve interaction between teachers and students, as well as facilitate active and enjoyable learning of mathematics. This study aims to develop a smart math board on the material of number arithmetic operations. The research method uses research and development with the ADDIE model. The subjects of this study were 3 elementary school students. The results of this study indicate that learning innovation using a smart board can improve students' motivation and learning outcomes of number arithmetic operations.